1997
DOI: 10.1002/(sici)1098-2361(1997)16:1<71::aid-zoo8>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

The effects of physical characteristics of the environment and feeding regime on the behavior of captive felids

Abstract: The behavior of captive felids is influenced by enclosure design and management regime. The behavior of nine felid species housed in 11 enclosures was recorded using instantaneous scan sampling. Stereotypic pacing was observed in 15 out of 19 individuals. Size of enclosure did not affect pacing behavior, but edges of enclosures were found to be used specifically for pacing behavior. Cats in relatively larger enclosures had a higher level of apparent movement, but only about 50% of enclosure space was used. Rai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(30 citation statements)
references
References 16 publications
3
25
0
2
Order By: Relevance
“…Stereotypic behavior has been well documented in zoo-housed animals [16, 17, 18, 19, 20, 21, 22, 23, 24, 25]. Several environmental factors, including space limitation [26, 27], effects of feeding schedule [1, 28], restraint of environmental control [29], and lack of stimulation [6, 30], have been identified in relation to the development of stereotypies [31, 32].…”
Section: Introductionmentioning
confidence: 99%
“…Stereotypic behavior has been well documented in zoo-housed animals [16, 17, 18, 19, 20, 21, 22, 23, 24, 25]. Several environmental factors, including space limitation [26, 27], effects of feeding schedule [1, 28], restraint of environmental control [29], and lack of stimulation [6, 30], have been identified in relation to the development of stereotypies [31, 32].…”
Section: Introductionmentioning
confidence: 99%
“…In Namibia, 'play trees' which are particular trees used for scent-marking, are important locations for territorial and communication behaviors [Marker-Kraus et al, 1996;Marker et al, 2003]. Lyons et al, [1997] found that raised areas were preferred sites within enclosures for captive felids, particularly for observation. This was also the case during the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Behavioral data were recorded pre-and post-treatment. Scan-sampling [Altman, 1974] was performed every 2 min for 3 hr to establish frequencies of predetermined mutually exclusive behaviors (Table 1) based on published large felid studies Lyons et al, 1997;Fishbacher and Schmid, 1999]. The behavioral categories of self-groom and aggression were recorded regardless of animal posture during the scan sample (i.e., if it was lying down and licking its paws, "self-groom" was recorded).…”
Section: Enrichment and Behavioral Observationmentioning
confidence: 99%